2020
DOI: 10.1097/md.0000000000021000
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide versus systemic corticosteroids in IgA Nephropathy

Abstract: IgA Nephropathy (IgAN) is characterized by mesangial deposition of dominant, polymeric, galactose-deficient IgA1 molecules of gut-associated lymphoid tissue origin. We sought to evaluate the efficacy of targeting the mucosal immune system dysregulation underlying IgAN pathogenesis with a pH-modified formulation of budesonide with a maximum release of active compound in the distal ileum and proximal colon. We did a retrospective study evaluating the efficacy of budesonide (Budenofalk) in the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…Targeted-release-formulation of budesonide (TRF-budesonide) has demonstrated promising results in terms of proteinuria and renal function in patients with immunoglobulin A nephropathy (IgAN) (1). Regarding its well tolerance, enteric budesonide may become the first step of immunosuppressive treatment of IgAN, although real world clinical practice publications are lacking (2)(3)(4). We evaluated the effect of budesonide in our cohort of patients affected by IgAN.…”
Section: Dear Editorsmentioning
confidence: 99%
“…Targeted-release-formulation of budesonide (TRF-budesonide) has demonstrated promising results in terms of proteinuria and renal function in patients with immunoglobulin A nephropathy (IgAN) (1). Regarding its well tolerance, enteric budesonide may become the first step of immunosuppressive treatment of IgAN, although real world clinical practice publications are lacking (2)(3)(4). We evaluated the effect of budesonide in our cohort of patients affected by IgAN.…”
Section: Dear Editorsmentioning
confidence: 99%
“… 12 At the same time, this kind of drug atomization inhalation can also prevent edema by contracting capillaries, inhibit the transfer of inflammatory cells to the site of inflammation attack, and thus prevent the occurrence or aggravation of airway inflammation in children. 13 Ismail G et al 14 showed that budesonide can effectively inhibit the redistribution of eosinophils and T lymphocytes in blood circulation, and plays an anti-inflammatory and immune function improvement role. Using budesonide by atomization inhalation can obtain more ideal lung absorption effect, improve drug concentration, ensure drug efficacy, reduce drug entry into blood circulation and reduce adverse drug reactions, especially for asthmatic children with relatively poor tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates a substantial systemic effect of TRF-budesonide and demonstrate that some amount of budesonide that is absorbed may act systemically rather than locally to attenuate albuminuria ( Glassock, 2017 ). Additionally, a retrospective, propensity-matched study evaluated the efficacy of budenofalk, a controlled-release formulation of budesonide, in 18 patients with IgAN in comparison with systemic corticosteroids ( Ismail et al, 2020 ). These results were consistent with the two aforementioned trials concerning albuminuria and renal function.…”
Section: Regulation Of Mucosal Immunity In Iganmentioning
confidence: 99%